2018
DOI: 10.1002/14651858.cd006922.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled steroids with and without regular salmeterol for asthma: serious adverse events

Abstract: Editorial group: Cochrane Airways Group. Publication status and date: New search for studies and content updated (conclusions changed), published in Issue 12, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 173 publications
1
11
0
Order By: Relevance
“…Combined low-dose ICS with LABA was found to improve asthma control for patient whose asthma is not controlled at step 2 and reduce asthma attacks (Evidence A). [ 134 135 ] The patient is recommended to continue on reliever treatment on “as-needed basis” (Evidence A). ICS with LABA are available (refer Medication Appendix) as follows:…”
Section: Section 6: Pharmacological Management In Adults and Adolescementioning
confidence: 99%
“…Combined low-dose ICS with LABA was found to improve asthma control for patient whose asthma is not controlled at step 2 and reduce asthma attacks (Evidence A). [ 134 135 ] The patient is recommended to continue on reliever treatment on “as-needed basis” (Evidence A). ICS with LABA are available (refer Medication Appendix) as follows:…”
Section: Section 6: Pharmacological Management In Adults and Adolescementioning
confidence: 99%
“… 10 Some studies reported that for every 1000 children treated with ICS for 23 weeks, 15 children experienced severe adverse effects. 26 …”
Section: Discussionmentioning
confidence: 99%
“…For patients receiving maintenance ICS treatment with as-needed SABA, adding LABA in a combination inhaler provides additional improvements in symptoms and lung function with a reduced risk of exacerbations compared with the same dose of ICS, 214,215 (Evidence A) but there is only a small reduction in reliever use. 216,217 Currently approved…”
Section: Preferred Step 3 Controller Options For Adults and Adolescentsmentioning
confidence: 99%